2020
DOI: 10.2478/spes-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Physical-motor development in children at elementary school: Article review

Abstract: SummaryPhysical development is the growth and change that occurs in a person’s body. The most obvious changes are changes in body shape and size. Meanwhile, motor development is the development of all forms of changes that occur progressively in a child’s ability to be able to perform various movements obtained through the interaction between maturity factors and training or experience during life which can be seen through changes/movements made. In the learning process, it appears that student activities are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…This concerted effort is designed to allow the body to move through the water at maximum speed. In other words, during swimming, some joints focus on maintaining stability while others use their wide range of motion to propel the body through the water at top speed (Tanaka and Seals, 1997;Susilowati, 2020). In the results of this study, a positive correlation was found between balance and free still swimming time and arm movement speed.…”
Section: Discussionsupporting
confidence: 48%
“…This concerted effort is designed to allow the body to move through the water at maximum speed. In other words, during swimming, some joints focus on maintaining stability while others use their wide range of motion to propel the body through the water at top speed (Tanaka and Seals, 1997;Susilowati, 2020). In the results of this study, a positive correlation was found between balance and free still swimming time and arm movement speed.…”
Section: Discussionsupporting
confidence: 48%
“…As for the components that make up of physical fitness there are several sub-aspects. Components of physical fitness include aspects of strength, endurance, flexibility, speed, balance, agility, accuracy, explosiveness and stamina (Bompa & Buzzichelli, 2019;Burhaein, Ibrahim, & Pavlovic, 2020;Susilowati & Suwarjo, 2020). Regular physical fitness exercises will bring benefits as.…”
Section: Introductionmentioning
confidence: 99%